Iklan Internet, Kualitas Status Jejaring Sosial (Face Book) Sebagai Media Marketing E-Commer B2C (Business To Consumer) Dan Interaksi Penjual & Pembeli Terhadap Keputusan Pembelian - Sjarifuddin Hasan (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2014)
Abstract: Every company engaged in the field of advertising media through the internet has opportunities and challenges in the move. This study is directed to observe the activities used in advertising through the internet, media quality facebook as a marketing medium in the e-commerce B2C (business to consumer) and the interaction between the seller and the buyer (customer) in deciding on the purchase of Batik Keris in Jakarta. This issue has subsequently been formulated in accordance with the data collection study variables, namely the advertising data over the internet, facebciok as its medium quality marketing B2C e-commerce, and the interaction between the seller and the buyer in the purchase decision Batik Keris. This data is compiled riding 100 respondents using a questionnaire and analyzed using regression analysis model. The results of the study showed that the quality of facebook as an intermediary media marketing and B2C e-commerce and the interaction between the seller and the buyer (customer) found positive and significant impact in deciding the purchase of Batik Keris in Jakarta.